REKOGNISI PENGALAMAN PEREMPUAN: STUDI KASUS PELAKSANAAN PASAL 4 PERMA NOMOR 3 TAHUN 2017 - Rika Saraswati (Arena Hukum, 2023)
Article 4 Supreme Court Regulation (Perma) No. 3 of 2017 on Guidelines for Judging Cases of Women in Conﬂict with the Law determines that judges should consider gender equality and non-discrimination, by identifying the facts in court hearing. The research question is to what extent the implementation of the article to the case under this study and its influence to the court verdict. The qualitative method is implemented in this study. The primary data collection was gathered by attending an online trial and the secondary data was obtained through a literature study by using the main documents of an infanticide case namely: the case file No. Pol: Bp/01/I/2020/Reskrim and the court decision No.37/Pid.B/2020/PN.Pwd. The result has demonstrated that judges had applied article 4 of PERMA during the court hearing. Judges’ considerations have recognized the experience of the woman perpetrator as the victim of sexual violence; however, judges insisted their decision on the basis of the actions of the perpetrator and ignored the psychological, sociological and imbalance power relations factors which were experienced by the woman.